Implementasi pendidikan pesantren salaf pada pondok pesantren khalaf di era globalisasi - Giantomi Muhammad; Asep Dudi Suhardini; Andewi Suhartini; Nurwadjah Ahmad E.Q Ahmad E.Q (At Turots: Jurnal Pendidikan Islam, 2023)
Islamic boarding schools are the oldest religious educational institutions that existed before the emergence of formal educational institutions in Indonesia. Two Islamic boarding schools are known, namely traditional and modern. Traditional Islamic boarding schools are identified as teaching religious values ​​with traditional approaches and methods. Modern Islamic boarding schools are identified as teaching religious values ​​with modern approaches and methods. These two types of Islamic boarding schools have their traditional characteristics. This study describes efforts to traditionalize modern pesantren education in the current climate of globalization. This research uses a qualitative approach with the literature study method. The results of the study reveal that modern Islamic boarding schools still adhere to and seek to develop traditional values ​​in terms of religious material, the creation of an educational atmosphere, and the relations between the parties involved, especially about the development of technology to form a quality civil society. Islamic development is also accompanied by a technology-based approach so that the students besides being able to form aspects of their faith and can have expertise in using technology as a basis for preaching.